Analisis Pengendalian Mutu Tapioka Menggunakan Metode Statistical Quality Control (SQC) (Studi Kasus PT XYZ) - Kemala, Lina; Fitriani, Fitriani; Saty, Fadila Marga (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
PT XYZ, located in Central Lampung Regency, is a company engaged in tapioca production. However, there are still instances of nonconforming products, particularly in RF (Reject Retained Mesh). The causes of RF include the decrease in starch content in raw materials, human error due to less careful workers, and environmental factors. This study aims to analyze the quality control of tapioca products at PT XYZ using the Statistical Quality Control (SQC) method. This method is applied to determine the extent to which product quality is controlled and to identify the factors causing product nonconformities. The analytical tools used include check sheets, histograms, control charts, Pareto diagrams, and fishbone diagrams. The data analyzed were obtained from observations, interviews, as well as production and defect data during February 2024. The results showed that the production process has not yet been fully within control limits, and the highest number of nonconformities occurred in the RF category. The main factors contributing to nonconformities include human, machine, method, raw materials, and environment. This study suggests that the company should improve operator training, machine maintenance, SOP supervision, raw material selection, and proper production scheduling. The implementation of effective quality control is expected to reduce the number of nonconforming products and improve overall product quality.